2013
DOI: 10.1038/cddis.2013.293
|View full text |Cite
|
Sign up to set email alerts
|

Enhancer of zeste homolog 2 activates wnt signaling through downregulating CXXC finger protein 4

Abstract: Through silencing tumor suppressor genes, epigenetic changes can activate signaling pathways important to cancer development. In this report, we found an epigenetic contribution to the aberrant activation of wnt signaling in human gastric cancer. CXXC4 (CXXC finger protein 4) was identified as a novel target of EZH2 (enhancer of zeste homolog 2), and EZH2 promotes the activation of wnt singaling by downregulating CXXC4 expression. CXXC4 inhibits the growth of gastric cancer cells both in vitro and in vivo thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
45
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 42 publications
5
45
0
Order By: Relevance
“…CXXC5 is overexpressed in a number of solid cancers (breast cancer, melanoma, thyroid cancer) and correlated with poor prognosis in breast cancer [84]. Furthermore, CXXC4 overexpression has been described in adenomas of the colon [85], whereas CXXC4 downregulation has been described in gastric carcinoma, where it associated with poor prognosis [86]. Future studies should examine whether overexpression or downregulation of CXXC4/5 proteins influences 5hmC levels in these types of cancer.…”
Section: Cxxc4/5 Expressionmentioning
confidence: 99%
“…CXXC5 is overexpressed in a number of solid cancers (breast cancer, melanoma, thyroid cancer) and correlated with poor prognosis in breast cancer [84]. Furthermore, CXXC4 overexpression has been described in adenomas of the colon [85], whereas CXXC4 downregulation has been described in gastric carcinoma, where it associated with poor prognosis [86]. Future studies should examine whether overexpression or downregulation of CXXC4/5 proteins influences 5hmC levels in these types of cancer.…”
Section: Cxxc4/5 Expressionmentioning
confidence: 99%
“…The upregulation of Fzd-3, Wnt palmitoyltransferase porcupine (PPN), and CDH17 has been found to be critical for cell proliferation and activation of the Wnt/ b-catenin signaling pathway in gastric cancer [78][79][80] . Moreover, Lu et al [81] have provided evidence indicating that EZH2 (histone methyl-transferase, enhancer of zeste homolog 2) activates Wnt signaling in gastric cancer mainly by downregulating the expression of CXXC4 (CXXC finger protein 4) without involving DNA methylation. It was also confirmed that overexpression of CXXC4 disrupts the association of Dvl with AxinGSK3b by directly interacting with Dvl, thus functioning as a tumor suppressor [81] .…”
Section: Wnt/b-catenin Pathway In Gastric Carcinogenesismentioning
confidence: 99%
“…Moreover, Lu et al [81] have provided evidence indicating that EZH2 (histone methyl-transferase, enhancer of zeste homolog 2) activates Wnt signaling in gastric cancer mainly by downregulating the expression of CXXC4 (CXXC finger protein 4) without involving DNA methylation. It was also confirmed that overexpression of CXXC4 disrupts the association of Dvl with AxinGSK3b by directly interacting with Dvl, thus functioning as a tumor suppressor [81] . Upregulation of Actin-binding protein anillin (ANLN), a protein involved in the cytokinesis and known to be dysregulated in many cancers, was found responding to the activity of Wnt/b-catenin pathway in gastric cancer [82] .…”
Section: Wnt/b-catenin Pathway In Gastric Carcinogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, according to a study from Korea, RNF43 gene might harbor mutational regional intratumoral heterogeneity (ITH), which could be accountable for tumorigenesis of GC (72). Lu et al (73) discussed that enhancer of zeste homolog 2 (EZH2) has ectopic expression in gastric cancer tissues. In a mechanistic manner, repressing CXXC finger protein 4 (CXXC4), a protein stabilize the degradation complex of β-catenin, was necessary for the contribution of EZH2 to GC.…”
Section: Wnt/β-catenin Pathway and Gastric Cancermentioning
confidence: 99%